2018
DOI: 10.18632/oncotarget.25331
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled breath analysis for gastric cancer diagnosis in Colombian patients

Abstract: We present here the first study that directly correlates gastric cancer (GC) with specific biomarkers in the exhaled breath composition on a South American population, which registers one of the highest global incidence rates of gastric affections. Moreover, we demonstrate a novel solid state sensor that predicts correct GC diagnosis with 97% accuracy. Alveolar breath samples of 30 volunteers (patients diagnosed with gastric cancer and a controls group formed of patients diagnosed with other gastric diseases) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…In that study, they reported 12 compounds (pentanoic acid, hexanoic acid, phenol, methyl phenol, ethyl phenol, butanal, pentanal, hexanal, heptanal, octanal, nonanal, and decanal) showing significantly higher concentrations ( p < 0.05) in the gastric cancer patients than in the noncancer controls. Durán-Acevedo et al ( 2018 ) employed in parallel gold nanoparticles (AuNP) gas sensor and gas chromatography mass spectrometry (GC-MS) to determine gastric cancer signatures in human breath. The GC-MS study resulted in the recognition of six VOCs that showed statistically significant differences between the cancer patients ( n = 14) and the control group ( n = 15).…”
Section: Introductionmentioning
confidence: 99%
“…In that study, they reported 12 compounds (pentanoic acid, hexanoic acid, phenol, methyl phenol, ethyl phenol, butanal, pentanal, hexanal, heptanal, octanal, nonanal, and decanal) showing significantly higher concentrations ( p < 0.05) in the gastric cancer patients than in the noncancer controls. Durán-Acevedo et al ( 2018 ) employed in parallel gold nanoparticles (AuNP) gas sensor and gas chromatography mass spectrometry (GC-MS) to determine gastric cancer signatures in human breath. The GC-MS study resulted in the recognition of six VOCs that showed statistically significant differences between the cancer patients ( n = 14) and the control group ( n = 15).…”
Section: Introductionmentioning
confidence: 99%
“…For performing this study, we built an electronic nose system comprising an array of cross-reactive chemical gas sensors based on organically-functionalized gold nanoparticles. This kind of sensors demonstrated very good suitability for detecting low VOC concentrations in biological samples, and room temperature operation that is a key feature of these nanomaterials [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the ease and less invasive nature of sampling from systemic biofluids such as plasma, serum, urine, saliva, sweat, and breath, most human studies have focused on these matrices, which typically are confounded with factors such as exposome, diet, internal and exterior microbiome, and the diverse genetic heterozygosity that make cancer epidemiological studies challenging. Newer matrices such as exhaled breath, exhaled breath condensate, and bronchoalveolar lavage fluid provide newer opportunities and challenges associated with sample preparation, metabolomic analysis, and assignment of metabolic biomarkers. However, these signals and biomarkers may or may not truly represent disease status, especially when conducted in underpowered study designs that fail to detect a true effect.…”
Section: Separating the Systemic Signal To Find Cancer Cell‐specificmentioning
confidence: 99%